FIRST ISOLATION OF Leptospira kirschneri SEROVAR CANICOLA AND Leptospira interrogans SEROVAR PYROGENES IN URINE SAMPLES FROM SLAUGHTERED CATTLE IN MIDWEST REGION OF SÃO PAULO STATE, BRAZIL - Manzini, Suzane [UNESP]; dos Santos, Wesley José [UNESP]; Guiraldi, Lívia Maísa [UNESP]; Aires, Isabella Neves [UNESP]; de Medeiros, Maria Izabel Merino [UNESP]; Pereira, Virginia BodelÃo Richini [UNESP]; Lucheis, Simone Baldini [UNESP] (My University, 2021)
Leptospirosis is a zoonosis of great importance in public health. One hundred and four urine samples from slaughtered cattle in Midwest region of SÃo Paulo State, Brazil were evaluated to detect Leptospira spp. The samples were kept in PBS and in cultures of EMJH and Fletcher. We observed growth of microorganisms in 13 samples of Fletcher medium, although it was not observed in EMJH medium. By PCR, 25 animals (samples) were positive with LEP1/LEP2 primers, which of them 16 samples were kept in PBS, six samples in Fletcher medium and three in EMJH medium. The 25 samples were submitted to PCR with the LipL32 gene to verify the pathogenicity. One sample amplified and by sequencing resulted in 99.77% of similarity to Leptospira kirschneri serovar Canicola and Leptospira interrogans serovar Pyrogenes. This is the first report of isolation of Leptospira kirschneri serovar Canicola and Leptospira interrogans serovar Pyrogenes from bovine urine sample in the Midwest Region of SÃo Paulo state, Brazil. We concluded the importance of leptospirosis in the herd evaluated and the attention for the occupational risk, because of the possibility of contaminated urine in the pastures and the spread of infection to other animals and contacting persons. kw]molecular diagnosis; slaughterhouses; leptospirosis.
(Primeiro isolamento de Leptospira kirschneriserovar canicola e Leptospira interrogans serovar pyrogenes em amostras de urina de bovinos abatidos na regiÃo Centro-Oeste do Estado de SÃo Paulo, Brasil)